2000
DOI: 10.1002/(sici)1097-0096(200006)28:5<211::aid-jcu1>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Sonography of palpable breast cancer

Abstract: Purpose. Because of the increasing use of sonography to rule out cancer in women with palpable breast abnormalities, this study was performed to determine the rate of sonographically occult malignancy in this clinical setting.Methods. Women who were recommended for biopsy based on mammographic and/or clinical findings underwent breast sonography. This study retrospectively analyzed the subset of patients with palpable malignant lesions. Lesions were classified as visible or occult on mammography and sonography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The reason behind higher sensi vity in our study might be due to the pa ents presented in advanced stages of the disease. In our study, the reason for referral for ultrasound was a 14,16 palpable mass in the breast similar to the previous studies. Kolb et al reported sensi vity of 78.6% whose pa ents were of younger age group (≤50 years) and had late stage of the 17 disease.…”
Section: Discussionsupporting
confidence: 87%
“…The reason behind higher sensi vity in our study might be due to the pa ents presented in advanced stages of the disease. In our study, the reason for referral for ultrasound was a 14,16 palpable mass in the breast similar to the previous studies. Kolb et al reported sensi vity of 78.6% whose pa ents were of younger age group (≤50 years) and had late stage of the 17 disease.…”
Section: Discussionsupporting
confidence: 87%
“…In a retrospective analysis of 293 palpable malignant lesions, sonography detected all cancers; 18 (6.1%) of these 293 cancers were mammographically occult. 15 In our series, sonography identified 2 palpable cancers (2 [14.2%] of 14) that were mammographically occult. Nineteen of the 60 lesions with suspicious findings were mammographically occult, as were 66 of the 165 benign abnormalities.…”
mentioning
confidence: 67%
“…Primary breast carcinoma and metastases to the breast in children and adolescents are extremely rare. [5][6][7] The primary tumors that most frequently metastasize to the breast are rhabdomyosarcomas, particularly the alveolar variety; non-Hodgkin's lymphoma; and leukemia. 2 Histiocytosis, medulloblastoma, neuroblastoma, renal carcinoma, urinary bladder carcinoma, and melanoma have also been reported to metastasize to the breast.…”
Section: Discussionmentioning
confidence: 99%